Ekspertyza w ujęciu procesowym i kryminalistycznym - Cieśla, Rafał (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
Both Polish legal literature and the case law have for long used the term of expertise. The notion was generally used in courts and the bodies carrying out preliminary proceedings. Yet, it is worth noting that until the code of criminal procedure of 1969 came into force the notion was not statutorily defined. The legislator uses the term of expertise in the binding polish code of criminal procedure of 1997 in art. 194 1–3 and in art. 198 § 3. It should be added that the legislator uses other terms to denote actions in connection with legal proceedings interchangeably with expertise: opinion, examination, observation of the mentally ill, inspection, autopsy, experiment or reconstruction to describe the so-called experimental reconstructions of the scene of crime. The notions are not very precise as they are used to describe different procedural activities, especially the notions of expertise, examination and opinion and says that they are most frequently used in science and practice. At the same time he opposes treating them as synonymous. Expertise should be understand in two ways. In the first meaning, sensu largo – an expertise consists of the activities performed by the expert and by the criminal proceedings authority, which include: taking the decision to perform the expertise on the initiative of the parties in the proceedings or own initiative; issuing a decision to perform the expertise; general supervision over the expertise by the criminal proceedings authority, which should be manifested in defining the scope of examination, the need to extend it, the need to use the methods which may result in damaging the examined material as is often the case in technical examination of documents and the deadline of the expertise; supervising the course of the expertise; informing the parties on issuing a decision to perform the expertise and on who was commissioned to perform it; evaluation of the expertise. In the other meaning, an expertise sensu stricto denotes the very activities undertaken by the expert examination, report, conclusion. Examination comprises observation of examined objects, experiments and documentation. Both observation and documentation of observation may be performed with appropriate specialist equipment. Documentation of the observations does not require equipment. Sometimes, however, without the use of equipment, documentation is not possible, just like the very examination e.g. in technical analysis of documents. In practice the most frequently encountered form of documentation is the description by hand, typewriter or computer. A report is a description of the expertise without an opinion, including the description of the course of examination and performed observations as well as the remaining important details connected with the expertise. [...]
Keywords: expertise; Polish procedure; Polish criminalistics